Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) Pegawai Pada Sekretaria DPRK Aceh Timur - Ismuhadi (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
The purpose of this study is to investigate how job satisfaction affects organizational citizenship behavior (OCB). Structural Equation Modeling, a sampling strategy using the total sampling method, and a sample size of 123 employees were used in this study's data analysis. According to his research, organizational citizenship behavior is positively and significantly impacted by job satisfaction (OCB). It is hoped that the management of the DPRK Secretariat of East Aceh Regency will continue to maintain and improve job satisfaction, for example: employee welfare, employee satisfaction with superiors, and promotions position, given that job satisfaction has a positive and significant effect on Organizational Citizenship Behavior (OCB) of the Secretariat of the DPRK East Aceh, East Aceh Regency.